Pengembangan Alat Penilaian Sikap Siswa dalam Pembelajaran Pendidikan Jasmani di SMU - Mu'arifin Mu'arifin (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This study was designed to develop an instrument to evaluate student's attitudes in Physical Education class. It applied a systemic approach by adopting and modifying an established model implemented in developing products. The result was a set of observation format used to measure and evaluate student's attitudes, together with indicators and descriptors of student's behavior in attending Physical Education class.